CORRUPTION RISKS IN THE TRANSPORT SECTOR - Завгородня, Лариса Олексіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The purpose: of the paper is to prevent, on the basis of institutional analysis, corruption risks as factors that negatively affect the behavior of a public servant and prevent them in the transport sector. Methods of research: using the logical semantic method of cognition allowed to investigate the definitions of anti-corruption concepts as the essence of corruption risks. Results: the preconditions for the emergence of corruption risks in the transport sector are determined, directions for their detection and prevention are offered. Discussion: problems in the field of prevention and counteraction to corruption, implementation of European standards of conduct of civil servants in the transport sector.